Perceptions of extreme programming an exploratory study. - Mi?ić, Vojislav B. (Software engineering notes.)
Extreme Programming (XP) is probably the best known and (arguably) the most controversial of the so-called agile software development methodologies. The paper presents the main findings of a small pilot survey about user perceptions of XP.